APUCEN ASSISTS NEPAL EARTHQUAKE VICTIMS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
Universiti Sains Malaysia (USM) through the AsiaPacific UniversityCommunity Engagement Network (APUCEN) with the cooperation of voluntary body MMICARE Association have provided assistance to the people of Nepal recently to help them to rebuild their lives after an earthquake measuring 7.8 on the Richter scale struck Nepal on April 25, 2015.